Validasi dan Penentuan Kadar Paracetamol dalam Jamu Pegal Linu yang Beredar di Pekanbaru Secara Spektrofotometri UV-Vis - Nadya Putri Auliya Serawaidi; Subardi Bali; Suci Aprilia (JURNAL FARMASI DAN MAKANAN, 2023)
Herbal medicine, a method of prevention and treatment based on nature, has been used for generations. Medicinal Chemicals (BKO) are added to conventional medicinal preparations to accelerate the therapeutic effect, because these products are in great demand by consumers. The distribution of herbal medicines containing BKO which is dangerous to the public is prohibited based on Minister of Health Regulation No. 007 of 2012. Herbal medicines for rheumatic pain and stiffness sold in Pekanbaru City will be analyzed for the BKO paracetamol content in this study. Sample b was found not to contain paracetamol, as determined through qualitative analysis using thin layer chromatography. For quantitative analysis using UV-Vis Spectrophotometry and this method was validated. The linear regression line equation obtained for paracetamol in the concentration range of 2-10 ppm is y = 0.0745x + 0.0422 which meets the SNI, AOAC and Eurachem criteria. The r value is 0.9993. The resulting recovery percentage range was 96.375 to 96.822, which meets AOAC specifications. The obtained RSD of 0.28% meets the specified criteria. The LOD calculation results obtained were 0.6523 parts per million (ppm), while the LOQ was 2.174 ppm. The results of UV-Vis spectrophotometric analysis show that samples a, c, d, e, and f contain paracetamol with concentrations of 3.54%, 6.65%, 7.71%, 6.00%, and 5.84% respectively.